2021
DOI: 10.1021/acssuschemeng.1c04866
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Power Use in the Cold Section of LNG Plants

Abstract: Liquefied natural gas (LNG) has garnered global attention as a relatively cleaner, environmentally more friendly, and more efficient energy source than other fossil fuels. Upgrading and liquefying natural gas to LNG is highly energy-intensive, and the most energy-consuming section of a typical LNG plant is its cold section. While much existing research has focused on heat integration and efficient refrigeration cycles to reduce power use in the cold section, energy sourcing for the cold section has received li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…16 The work implementing integrated alternatives systems for LNG/NGL production reported an SPC of 0.4 kWh/kg LNG. 17 Whereas the energy optimization of the cold section in another study deploying double-column NRU and heat integration reported specific energy consumption of 0.27 kWh/kg LNG, 5 our work methodology results in the lowest specific energy consumption (0.24 kWh/kg LNG) among these studies, highlighting the importance of UN rem technique. Abbreviations: LNG, liquefied natural gas; SPC, specific power consumption.…”
Section: Optimization Of Upfront Nitrogen Removalmentioning
confidence: 71%
See 3 more Smart Citations
“…16 The work implementing integrated alternatives systems for LNG/NGL production reported an SPC of 0.4 kWh/kg LNG. 17 Whereas the energy optimization of the cold section in another study deploying double-column NRU and heat integration reported specific energy consumption of 0.27 kWh/kg LNG, 5 our work methodology results in the lowest specific energy consumption (0.24 kWh/kg LNG) among these studies, highlighting the importance of UN rem technique. Abbreviations: LNG, liquefied natural gas; SPC, specific power consumption.…”
Section: Optimization Of Upfront Nitrogen Removalmentioning
confidence: 71%
“…Within the LNG plant, the cold section is the pillar of the liquefaction process and consumes roughly 60% of the total energy demand. 5 This section is composed of the refrigeration cycles (C3MR or SMR, etc. ), fractionation unit, nitrogen removal unit (NRU), and helium extraction unit.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gas stream is cooled by a complex web of heat exchangers, pumps and compressors, fractionation units, and phase separation units, which use the propane and refrigerant cycles. According to Pal et al, 84 the energy cost of the cold section is reported to be approximately 60%. However, the cost can be optimized with improved resource management, structural design changes, and mathematical optimization techniques.…”
Section: Economic Considerationsmentioning
confidence: 99%